Managing women with complex presentations: How to approach concomitant prolapse and voiding dysfunction - Kelleher, Cornelius (Canadian Urological Association Journal, 2013)
Concomitant pelvic organ prolapse and voiding difficulties (e.g., incontinence) can both be corrected surgically at the same time. Voiding dysfunction secondary to incontinence surgery is uncommon, but does occur even in the most experienced hands. Surgical re-intervention can correct these post-surgical voiding difficulties.